Peace By Pieces: The Politics Of Herdsmen’s Attacks, Grazing Policy And The Ekiti State Grazing Regulation Law, 2016 - Olugbenga, Ebenezer Olatunji (Advances in Social Sciences Research Journal, 2017)
This paper examines the politics of the ‘Prohibition of Cattle and other Ruminants Grazing in Ekiti State Law, No. 4 of 2016’ against the background of incessant attacks by itinerant pastoralists (or herdsmen) on farmers and host communities in different parts of Nigeria. Such attacks have claimed many lives, destroyed farm crops, other properties and sacked entire communities in the country. The author notes that such attacks/conflicts are dangerous to peaceful cohabitation among the numerous ethnic groups in Nigeria and can threaten national peace, unity and progress. Relying on the organized anarchy model of policy analysis, the author relies mainly on the strength of secondary (including historical) and to a lesser extent, primary sources of data to situate such conflicts at the intersection of economic, climate change, ethnic and historical/political factors in a multi-ethnic, federal Nigerian state. The author posits that many leaders of the Nigerian political class have been playing politics in their responses to the attacks and that, in a manner descriptive of seeking peace by pieces, only a few who are genuinely concerned about lasting peace, security and national unity have been pushing for legitimate means of bringing the attacks under control. The author argues that Nigeria will have to seek solutions to the problem within its specific circumstances and historical experiences. It therefore makes recommendations on ways to bring the attacks under control with a view to building a stronger, more united Nigeria.